Thick Film Circuits: Present State and Future Development. (1981) - Novotny, J.
Abstract : Thick film technology has been known for about 20 years. The technique of inks, printing, firing and trimming has grown in this time to a well established state of the art. This paper gives an overview of the status today and an outlook into the future, not only for thick film, but also for hybrids built out of thick film circuits with incorporation of additional components. The paper gives the main market figures and market segments for thick film applications and mentions the main reasons for this. New fields of applications for thick film will be found in the future where considerations like reliability, space savings and cost advantage are of importance.